2017
DOI: 10.1111/jnc.13919
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of chemokine CXCL11 in the development of morphine tolerance in rats with cancer‐induced bone pain

Abstract: Morphine is viewed as one of the classical treatments for intractable pain, but its role is limited by side effects, including analgesic tolerance. A few chemokines have been reported to be engaged in the mechanisms of morphine tolerance. However, the exact roles of CXC chemokine 11 (CXCL11) in chronic morphine tolerance remain unknown. In this study, Walker 256 mammary gland carcinoma cells were inoculated into the tibia of rats to provoke cancer-induced bone pain. Then, morphine was intrathecally administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 67 publications
(64 reference statements)
2
21
0
Order By: Relevance
“…The ED 50-Ipsilateral of morphine in this model (1.3 mg/kg) was found to be higher than that in a cisplatin induced peripheral neuropathy model (0.8 mg/kg; s.c.) (Han et al, 2014), similar to that in a neuropathic pain model of spared nerve injury (1.2 mg/kg; s.c.) (Zhao et al, 2004), but lower than that in nociceptive paw pressure test (2.8 mg/kg; s.c.) (Morgan et al, 2006) in rats. Our findings are aligned with others who showed that morphine is effective in alleviating pain hypersensitivities in this model (Guo et al, 2017; Liu et al, 2017). In other work, spinal levels of endomorphin-2, an endogenous ligand at μ-opioid receptors, were reduced following ITI of W256 cells, and this was correlated with development of mechanical allodynia in these rats (Chen et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…The ED 50-Ipsilateral of morphine in this model (1.3 mg/kg) was found to be higher than that in a cisplatin induced peripheral neuropathy model (0.8 mg/kg; s.c.) (Han et al, 2014), similar to that in a neuropathic pain model of spared nerve injury (1.2 mg/kg; s.c.) (Zhao et al, 2004), but lower than that in nociceptive paw pressure test (2.8 mg/kg; s.c.) (Morgan et al, 2006) in rats. Our findings are aligned with others who showed that morphine is effective in alleviating pain hypersensitivities in this model (Guo et al, 2017; Liu et al, 2017). In other work, spinal levels of endomorphin-2, an endogenous ligand at μ-opioid receptors, were reduced following ITI of W256 cells, and this was correlated with development of mechanical allodynia in these rats (Chen et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Despite a plethora of available potential treatment options for chronic pain, opioids are still the gold standard for its pharmacological management in the clinical setting. However, long-term use of these drugs is often limited due to the development of opioid tolerance or opioid-induced hyperalgesia(OIH), characterized as progressive loss of analgesic potency after continuous morphine exposure that necessitates dose escalation to achieve equal pain relief [119][120][121][122][123]. μ-opioid receptors (MOR) is a GPCR existing in the superficial dorsal horn of the spinal cord.…”
Section: Pi3k/akt Pathway and Opioid Tolerance And Hyperalgesiamentioning
confidence: 99%
“…The ED50-Ipsilateral of morphine in this model (1.3 mg/kg) was found to be higher than that in a cisplatin induced peripheral neuropathy model (0.8 mg/kg; s.c.) (Han et al, 2014a), similar to that in a neuropathic pain model of spared nerve injury (1.2 mg/kg; s.c.) (Zhao et al, 2004), but lower than that in nociceptive paw pressure test (2.8 mg/kg; s.c.) (Morgan et al, 2006) in rats. Our findings are aligned with others who showed that morphine is effective in alleviating pain hypersensitivities in this model (Guo et al, 2017, Liu et al, 2017a. In other studies, mRNA and protein levels of μ-opioid receptors in the spinal dorsal horn and dorsal root ganglia of rats were reduced following unilateral ITI of W256 cells in this model (Yao et al, 2016, Hou et al, 2017.…”
Section: Trabecular Number (Tbn)supporting
confidence: 92%